Global anthropogenic effects on meteorological—hydrological—soil moisture drought propagation: historical analysis and future projection - Wang, S.; Huang, S.; Wang, C.; Zhang, X.; Wu, J.; Gulakhmadov, A.; Niyogi, D.; Chen, N. (Elsevier, 2025)
Intensified anthropogenic activities in the 21st century have introduced profound and widespread impacts on drought dynamics and their propagation. However, the extent to which large-scale human-induced forces, such as greenhouse gas emissions (GHGs) and aerosols, influence the propagation of drought from meteorological to hydrological and soil moisture droughts at the global level remains insufficiently understood. To address this gap, we conducted a comprehensive quantitative analysis, integrating historical simulations of various anthropogenic and climatic drivers with future projections based on different Shared Socioeconomic Pathways (SSPs) from the CMIP6. Key features of drought propagation—such as propagation time, probability, and drought characteristics—were assessed across distinct historical and future scenarios to elucidate the anthropogenic influences. The findings indicate that human-driven forces, particularly GHG emissions, have significantly influenced both meteorological-hydrological and meteorological-soil moisture drought propagation. Notably, anthropogenic factors led to a general reduction in drought propagation time, with GHGs playing a dominant role. Furthermore, GHG emissions were found to markedly increase the probability, duration, and severity of propagated droughts, especially across northern North America, southern Africa, and northeastern Asia. Future projections reveal a slight decline in meteorological-hydrological drought propagation probability during 2015–2100, while meteorological-soil moisture drought propagation probability shows a pronounced upward trend. Additionally, our analysis underscores the critical role of global warming and vegetation changes in shaping drought propagation patterns. These results offer valuable insights for enhancing drought early warning systems in a changing climate.